2000
DOI: 10.1007/s003300000491
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary MALT lymphoma: imaging findings in 24 cases

Abstract: IntroductionPulmonary B-cell non-Hodgkin's lymphomas, although rare, are now well recognised as primary lung neoplasms. They have previously been classified according to nodal classification systems, [1,2,3,4] but are currently thought to be primary extranodal lymphomas, mainly of low grade, which arise from bronchial mucosa-associated lymphoid tissue (MALT) [5,6,7,8]. These are analogous to extranodal MALT lymphomas, which were first described in the stomach [9] and are now known to arise at numerous other mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 29 publications
7
73
0
Order By: Relevance
“…7) In some patients, mediastinal lymph node enlargement and a pleural effusion can be seen but can also increase the difficulty in differentiating pulmonary MALT lymphoma from pneumonia, tuberculosis, and lung cancer. 8) In this study, the imaging findings were consistent with that of those reported in medical literature. Pulmonary consolidation is now considered the most common imaging manifestation; in particular, pulmonary MALT lymphoma should be considered if pulmonary consolidation is revealed by a bronchogram.…”
Section: Imaging Featuressupporting
confidence: 90%
“…7) In some patients, mediastinal lymph node enlargement and a pleural effusion can be seen but can also increase the difficulty in differentiating pulmonary MALT lymphoma from pneumonia, tuberculosis, and lung cancer. 8) In this study, the imaging findings were consistent with that of those reported in medical literature. Pulmonary consolidation is now considered the most common imaging manifestation; in particular, pulmonary MALT lymphoma should be considered if pulmonary consolidation is revealed by a bronchogram.…”
Section: Imaging Featuressupporting
confidence: 90%
“…The British Journal of Radiology, July 2012the lesion margin have been reported in MALT lymphoma [20], but these are non-specific findings seen in a number of other conditions, including bronchoalveolar cell carcinoma. Parenchymal lesions are usually bilateral (60-70%) and multiple (70-77%), and nearly all the lesions contain air bronchograms [21].…”
Section: Imaging Findingsmentioning
confidence: 99%
“…The disease occurs most commonly in elderly men aged 60-80 [134,135]. Some of the patients have a history of autoimmune disorders (Sjogren's disease, rheumatoid arthritis) [137,138]. About 40% of patients are asymptomatic and present with a solitary pulmonary nodule on chest x-ray.…”
Section: Lungmentioning
confidence: 99%